How to Build a Super Vocabulary - Chin, Beverly Ann (John Wiley & Sons, 2014)
The English language is huge, immense, enormous, titanic, prodigious. (All of these words mean “very large.”) The big, fat unabridged dictionaries have about half a million entry words. Language experts estimate that English may have as many as a million words if you count scientific and technical terms. And like all living languages, English keeps growing all the time. So how many English words do you know already? Probably many thousands. But just as you wouldn’t stay with the vocabulary you had when you were two or three years old, you won’t stay with the one you have now. Your vocabulary will keep growing as you meet new words in your reading and hear them in conversations, on radio, or on TV. Your vocabulary is directly related to your success in school. That’s why there are so many vocabulary questions on state and national standardized tests. Readers who evaluate your writing on essay tests also focus on your vocabulary, to make sure you use words precisely and correctly. The book you are holding, How to Build a Super Vocabulary, is a resource and reference book that can help you enlarge your vocabulary. It introduces you to many new words to use when you write, read, speak, and listen.